(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
For the past few years, it is seen that most of the companies are facing the pressure to provide the information regarding their performance based on environmental, social and governance (ESG) issues. Although there are very limited studies which has focused on the optimal ways to construct sustainability based portfolios. This papertries to reduce this gap by incorporating the ESG constraint in portfolio optimization. The objective of the study is to construct an optimum portfolio by using the basic Markowitz mean-variance optimization model and the modified mean variance model with sustainability constraint in order to make a comparative evaluation of basic Markowitz model and proposed mean variance optimization model with ESG constraint in Indian Capital Market. The study shows that the modified mean variance model with sustainability constraint is very much effective in the Indian capital market rather than the basic Markowitz optimization model.